A Study of the Psychological Status of Couples Attending Infertility Clinic of a Tertiary Healthcare Institution of New Delhi - Vijayan, Sruthi M.; Rasania, Sanjeev K.; Acharya, Anita S.; Rasheed, Nazish; Saxena, Pikee (Indian journal of community medicine, 2025)
Background: Globally, there are 48 million couples and 186 million individuals who live with infertility, and in India, there are approximately 22-23 million infertile couples. Infertility and its treatment can negatively influence the couple's psychological well-being which in turn could affect their fertility and treatment outcome. Most of the studies have focused on the psychosocial stress among women due to infertility and very few studies have seen the impact it has on men. Hence, the objective of the study is to assess the psychological status of the couples attending the infertility clinic of a tertiary healthcare institution. Materials and Methods: Couples attending the infertility clinic of Smt. Sucheta Kriplani Hospital (SSKH), New Delhi, were included. The study period was from January 2021 to June 2022. A semi-structured, self-designed interview schedule was used to collect information from study subjects. The DASS-21 questionnaire was used to assess subjects' psychological status. Results: The prevalence of depression, anxiety, and stress was higher among wives as compared to husbands (P value < 0.1 in all three psychological states). Depression, anxiety, and stress were found to be more in husbands and wives with primary infertility as compared to those with secondary infertility (however, this finding was found to be significant only in wives in relation to depression, P < 0.05). Conclusion: In general, the prevalence of depression, anxiety, and stress was higher in wives as compared to husbands.